Selective Fusions for Primary Midfoot Osteoarthritis. Issue 2 (June 2016) - Bariteau, Jason T.; Fantry, Amanda; Tenenbaum, Shay
Abstract : Midfoot arthritis is a common condition presenting to foot and ankle specialists. Primary osteoarthritis of the midfoot demonstrates a unique combination of symptoms and radiographic changes, most commonly involving the second tarsometatarsal, the third tarsometatarsal, and the medial facet of the naviculocuneiform joints. Operative intervention typically involves fusing the arthritic joints. This paper reviews the important steps for a successful outcome, discusses the common complications, and delineates a typical postoperative protocol. Level of Evidence: Diagnostic Level 5. See Instructions for Authors for a complete description of levels of evidence.